Experimental analysis on water pipe turbine-generator design parameters - Nurulamni, Md Mukhtar (2013)
The objective of the study is to develop a small-scale water pump based test bed and to do prototyping of various turbine designs based on various parameters. As the energy demand of industry grows exponentially, fabrication of hydraulic energy system becomes a crucial point of concern. Many research activities about hydraulic have been carried out by experimental methods and by theory and simulation. Hydro energy parameters have been used to study the relation between the hydro energy parameters and subsequent relative output energy. The results obtained by the experimental results, performed in prototype model. In this work different parameters have been used to tap water. The water injected by nozzle on blades of hydraulic turbines. Efficiency and maximal power output are two of the most important goals to analyze in hydraulic turbines. The efficiency of water turbines are most frequently expressed using the power output at the alternator. To perform the calculation of efficiency is necessary to know several parameters such as kinetic and potential energy of water due to the position, because of this is required to know the flow rate entering the turbine. The flow rate of water through the turbine (Q) is determined by the volume of water flowing in time unit. As a conclusion, this project is quite successful because it is able to fulfill all of the objectives stated and also performing up to expectation